The representation of younger age cohorts in Asian parliaments: Do electoral systems make a difference? - JOSHI, Devin K. (Institutional Knowledge at Singapore Management University, 2013)
This study examines the descriptive representation of younger age cohorts in Asian parliaments. Drawing from literature on women's parliamentary representation, it develops the hypothesis that proportional representation (PR) elections provide more incentives for the inclusion of younger representatives than do single-member district plurality (SMDP) electoral systems. Analysing an original dataset of over four thousand MPs from 14 countries, I find support for the argument that PR electoral systems favour the election of younger MPs even after controlling for multiple alternative explanations.